Desain Sistem Informasi Pemasaran Produk Agroindustri Berbasis Website Edukasi Pada Gapoktan Minggirsari Blitar (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2023)
The rapid development of internet technology in the modern era has not been fully utilized by farmers resulting in economic disparities among farmers due to product sales through extended supply chains so that there are significant differences in prices for agro-industrial commodities at the farmer and market levels. Meanwhile, farmers are still less interested in reading, resulting in limited knowledge of processing agricultural products to increase economic value. The research aims to design a sales and education system and produce a website for marketing agro-industry products based on an educational website that is good enough. The study was carried out in several stages, namely problem identification, website design using the waterfall method, website testing using the black box method, making questionnaires based on the user acceptance test (UAT), validity and reliability tests, distributing website acceptance questionnaires by users based on the user acceptance test (UAT) and data processing. The research results are to get a website design that combines sales and education systems in one website that is already running well by getting a 100 percent score when tested internally using the black box method. Website acceptance test by users using the user acceptance test (UAT) method results in a design factor of 77.86%, a content factor of 78.75%, and a usability factor of 78.24%. The real test for the entire website scores 78.2% and is included in the good category to be accepted in society.
Keywords: farmer; blackbox; user acceptance test (UAT); website; technology